2023
DOI: 10.1186/s13058-023-01725-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipidome of mammographic breast density in premenopausal women

Kayla R. Getz,
Myung Sik Jeon,
Chongliang Luo
et al.

Abstract: Background High mammographic breast density (MBD) is a strong risk factor for breast cancer development, but the biological mechanisms underlying MBD are unclear. Lipids play important roles in cell differentiation, and perturbations in lipid metabolism are implicated in cancer development. Nevertheless, no study has applied untargeted lipidomics to profile the lipidome of MBD. Through this study, our goal is to characterize the lipidome of MBD in premenopausal women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Volumetric percent density (VPD) has emerged as a quantitative standard for assessing MBD. Previous study revealed that lipid species inversely associated with VPD predominantly belonged to the triacylglycerol ( N = 43) and diacylglycerol ( N = 7) sub-pathways [ 56 ]. These lipid species align with the protective effects observed in our research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volumetric percent density (VPD) has emerged as a quantitative standard for assessing MBD. Previous study revealed that lipid species inversely associated with VPD predominantly belonged to the triacylglycerol ( N = 43) and diacylglycerol ( N = 7) sub-pathways [ 56 ]. These lipid species align with the protective effects observed in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have predominantly explored triglycerides as a whole without specific subdivisions based on their structural forms. Hence, further research is warranted to identify which specific structural forms of triglycerides can exert preventive effects [ 56 ]. Our study highlights the potential importance of triglyceride subtypes in modulating BC risk, particularly in different molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%